Practical aspects of real-time reaction monitoring using multi-nuclear high resolution FlowNMR spectroscopy. Issue 24 (28th September 2016) - Hall, Andrew M. R.; Chouler, Jonathan C.; Codina, Anna; Gierth, Peter T.; Lowe, John P.; Hintermair, Ulrich
Abstract : FlowNMR spectroscopy is an excellent technique for non-invasive real-time reaction monitoring under relevant conditions that avoids many of the limitations that bedevil other reaction monitoring techniques. Abstract : FlowNMR spectroscopy is an excellent technique for non-invasive real-time reaction monitoring under relevant conditions that avoids many of the limitations that bedevil other reaction monitoring techniques. With the recent commercial availability of FlowNMR hard- and software solutions for high resolution spectrometers it is enjoying increased popularity in both academia and industry. We present an account on practical aspects of high field multi-nuclear FlowNMR for reaction monitoring including apparatus design, flow effects, acquisition parameters and data treatment, which are important to consider if accurate kinetic data are to be obtained from FlowNMR experiments. Flow effects on NMR peak areas are particularly important as they can lead to large quantification errors if overlooked, but can easily be corrected for and even used to increase temporal resolution with suitably adjusted instrument settings.